A proteção constitucional da liberdade ante a religiosidade do terceiro milênio: os desafios enfrentados pelo Supremo Tribunal Federal - Balera, Felipe Penteado (2018)
Fundamental rights are in progressive evolution in order to guarantee, as soon as possible, equal freedom for all. In this way prejudices and unreasonable discriminations from the constitutional point of view must be overcome to achieve the greatest yearning of humanity, which is collective happiness. Religions and modes of religiosity have also developed and changed in the modernity, allowing the emergence of new beliefs and various types of religious intensity, each of which is composed of values and dogmas, sometimes seemingly non-conciliatory with the happiness of other religious groups or social policies. The freedom to believe, worship and express religion, with any intensity, is part of the advancement of fundamental rights, being guaranteed in the Federal Constitution of 1988. This dissertation attempts to present conciliatory solutions to the conflict between religious freedom and other fundamental rights, appreciating the constitutional law and the most recent challenges faced by the Supremo Tribunal Federal